Nature Archetypes – Concepts Related to Objects and Phenomena in Natural Environments. A Swedish Case - Ottosson, Johan; Grahn, Patrik (Frontiers in Psychology, 2021)
Do people classify nature in ways that can be described as archetypes? Could it be that these can be interpreted as health promotive? More and more researchers today suggest that archetypes can be used to analyze, describe, and develop green spaces. In parallel, an increasing number of research results since the 1980s have shown that human health and well-being are positively affected by stays in certain nature areas. The qualities in these nature areas which stand out to be most health-promoting are interpreted to be properties of nature that humans through evolution are prepared to perceive in a positive way. In this study, 547 respondents in southern Sweden answered a questionnaire on properties in natural areas. Through cluster analysis, these properties have been grouped into 10 types of nature and landscape. The 10 clusters are related to specific phenomena and places in Scandinavian nature, which could be described as archetypal. These natural phenomena and places are discussed, partly based on references to archaic Scandinavian mythology, Scandinavian lifestyle, and cultural canon, and partly on research on evolution, human preferences, and how nature can affect human health. We discuss how these nature archetypes evoke anxiety, fear, and distancing as well as calmness, tranquility, and connection. However, researchers have so far focused on how visits to natural environments have affected the sympathetic nervous system, and not realized the possibility of including the calm and connection system as well as the oxytocin in their explanatory models. In a follow-up article, we intend to develop a model for how the nature archetypes can interact with the calm and connection system.